STRATEGI KOMUNIKASI POLITIK DIGITAL PASCA-KEBENARAN - Andika Hendra Mustaqim (Jurnal Dakwah Risalah, 2018)
Post-truth in politics when it is warming up with various phenomena. The research objective revealed and explored in this study is how post-truth digital political communication strategies. The research method uses descriptive qualitative with a qualitative approach with critical paradigm and analysis. The post-truth political communication strategy that will be delivered is applicable and can be applied in the practice of political communication. The strategies are fake news: between facts and lies; near-lie: use the right words to form wrong impressions; deception with self delusion; spin: favorable interpretation of facts; euphemasia; repetition; personalization; and ignoring rationality, prioritizing emotions. The digital political communication strategy is more focused on how to use digital media for the benefit of political communication. The strategies are blogging; influencing public opinion; social media: building enggage and closeness; and mainstream media; focusing entertaining and attractive. These three strategies are based on digital media that are fully utilized in terms of digital political communication post-truth.